INDUSTRI RUMAH TANGGA KONVEKSI PAKAIAN ANAK SEBAGAI BENTUK EKONOMI KREATIF MASYARKAT KAMPUNG PULO KALIBATA KELURAHAN KALIBATA KECAMATAN PANCORAN JAKARTA SELATAN - Ryan Gumilang, Ibnu (Humanis, 2014)
Clothing is a basic human needs, in addition to food and shelter. One of the central areas of the apparel industry in South Jakarta child is Kampung Pulo, Kampung Pulo Kalibata that initially people's livelihood are growers of fruits and vegetables. Along with the increasing needs of life and the rapid development ofJakarta so many people are selling their land because of unfavorable life as a farmer. The money from selling the land, they used to buy a sewing machine and initiating convection and grow until now which is a form of creative community in maintaining the economic stability of the family. Based on the description above issues examined in this study as follows: the basic motivation of the community to develop convection, how the activity of convection industrial business, how the business implications of industrial convection. This research was conducted by using qualitative methods, which were analyzed with the theory put forward by David C. Mclelland concept of 'Need For Achievement'.
Keywords: Creative Economy, Industry Household, Kids Apparel Convection.